MINAT MASYARAKAT MELAYU DALAM MELESTARIKAN BUDAYA MANDI TAMAN DI DESA BANTAN SARI KABUPATEN BENGKALIS - Nurul Sahida; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the existence of Taman Mandi Culture in the community of Bantan Sari Village, Bengkalis Regency, in which the Taman Mandi Culture in essence reflects gratitude for the ongoing marriage and the union of husband and wife. In the Taman Mandi Culture, there are many meanings contained therein which aim to clean oneself from all the stains that have been done during adolescence, besides the efforts to pray for prayers so that the newly built ark will be eternal and happy with being blessed with pious and pious offspring. But at this time the Taman Mandi itself is very rarely preserved. The formulation of the problem in this study are How is the interest of the Malay community in preserving the Taman Mandi Culture in Bantan Sari Village, Bengkalis Regency and What factors cause the lack of interest of the Malay community in preserving Taman Mandi Culture in Bantan Sari Village, Bengkalis Regency. The objectives of this research are to Know how the interest of the Malay community in preserving Taman Mandi Culture in Bantan Sari Village, Bengkalis Regency and to Know what factors cause the lack of interest of the Malay community in preserving the Taman Mandi Culture in Bantan Sari Village, Bengkalis Regency. Data collection techniques in this study were observation, interviews and documentation. Respondents of this study were 5 people, namely 1 head of the Bantan Sari Village Traditional Malay Institution, 2 Public figure and 2 Bantan Sari Village people. The data analysis technique in this study is a qualitative method. The result of this research is that the interest in enlivening the implementation of Taman Mandi Culture is very high, but there is very little interest in holding this culture, this is due to several internal factors and external factors. Internal factors include 1. Lack of public knowledge about the Garden Bathing Culture. 2. Economic aspects of the community. 3. Time for garden bathing. 4. The role of the mak andam. Meanwhile, the external factors are There are cultural influences from other communities.Key Words: The Culture Of Garden Bath, The Melayu Community